Self-efficacy with medication adherence in the elderly with hypertension - Maria Kurni Menga; Yohan Trayanus Lasarus Djaha (Journal Interdisciplinary Health, 2025)
Introduction: Hypertension is a common chronic condition among the elderly that requires long-term pharmacological management. Medication adherence is crucial in maintaining blood pressure control and preventing complications. One psychological determinant that plays an important role is self-efficacy, which refers to an individual's belief in their ability to perform specific behaviors, including adhering to prescribed medication regimens. This study aimed to examine the relationship between self-efficacy and medication adherence among elderly patients with hypertension. Methods: This study employed a cross-sectional quantitative design. A total of 100 elderly hypertensive patients were selected using purposive sampling at Public Health Center X. Data were collected using the General Self-Efficacy Scale (GSES) and the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using Spearman’s correlation test. Results: The results showed that most respondents had a moderate level of self-efficacy (58%) and a moderate level of medication adherence (62%). A significant relationship was found between self-efficacy and medication adherence (p = 0.001; r = 0.462), indicating a moderate positive correlation. Conclusions: Self-efficacy is significantly and positively associated with medication adherence in elderly patients with hypertension. Enhancing self-efficacy through health education, family support, and interdisciplinary interventions is essential for improving hypertension management among the elderly